Foreign Capital in Polish Banks – Its Contribution to Systemic Risk and Level of Concentration - Jan Koleśnik (Annales Universitatis Mariae Curie-Skłodowska Sectio H, Oeconomia, 2023)
Theoretical background: An important source of systemic risk in the banking system is the ownership structure, especially the ratio of foreign capital, which affects not only the results of individual banks but also the situation of the entire sector during the financial crisis. The effects of foreign capital engagement in a local banking system not always have to be exclusively positive. In particular, this refers to the systemic risk contribution of foreign capital in the national banking system as well as foreign capital concentration and potential systemic risk transfer through foreign capital. These threats are becoming especially important for the Polish banking sector, where foreign capital to assets ratio – despite its gradual decrease since 2008 – is still higher than 40%.